THE URBAN SUFISM, SOCIAL MOVEMENT AND THE ‘SMILING’ ISLAM: A case study of “Hubbun Nabi” Kartasura, Sukoharjo - Mibtadin Mibtadin (Analisa: Journal of Social Science and Religion, 2018)
The urban sufism movement namely Hubbun Nabi becomes an interesting phenomenon since it emerges in the midst of Islamic-militant religious movement which is symptomatic in Sukoharjo. Hubbun Nabi represents the unity of many denominations whose Islamic understandings are Ahlussunnah wal Jama’ah (Aswaja) of Nahdliyin in Sukoharjo. It carries a moderate religious style. This research portrayed the style of moderate religiosity which is developed by Majlis Dzikir and Sholawat Hubbun Nabi. It was a descriptive-qualitative research. The techniques of collecting data are direct observation on the activities of Majlis Dzikir and Sholawat Hubbun Nabi, in-depth interview to Kyai Abdulloh Faishol, and documentation. Data was analyzed by reducing and displaying data, then drawing conclusion. Data validation was processed through triangulation method and informant review. Sukoharjo is one of the important cities for it has long been the basis of radical and moderate movements. One of the local movements in Sukoharjo whose rapid development was Majlis Dzikir and Sholawat Hubbun Nabi. The core values carried out by Hubbun Nabi movement are moderatism and tolerance, open-mindness, respecting plurality, and anti-fanaticism. Hubbun Nabi has indeed a significant role in the process of de-radicalization of the religious movement through transforming the values into the wider community. Hubbun promotes moderate Islam, the theology of humanity as a form of the “smiling of Islam.”